Differential CD147 Functional Epitopes on Distinct Leukocyte Subsets - Pata, Supansa; Surinkaew, Sirirat; Takheaw, Nuchjira; Laopajon, Witida; Chuensirikulchai, Kantinan; Kasinrerk, Watchara (Frontiers in Immunology, 2021)
CD147, a member of the immunoglobulin (Ig) superfamily, is widely expressed in several cell types. CD147 molecules have multiple cellular functions, such as migration, adhesion, invasion, energy metabolism and T cell activation. In particular, recent studies have demonstrated the potential application of CD147 as an effective therapeutic target for cancer, as well as autoimmune and inflammatory diseases. In this study, we elucidated the functional epitopes on CD147 extracellular domains in T cell regulation using specific monoclonal antibodies (mAbs). Upon T cell activation, the anti-CD147 domain 1 mAbs M6-1E9 and M6-1D4 and the anti-CD147 domain 2 mAb MEM-M6/6 significantly reduced surface expression of CD69 and CD25 and T cell proliferation. To investigate whether functional epitopes of CD147 are differentially expressed on distinct leukocyte subsets, PBMCs, monocyte-depleted PBMCs and purified T cells were activated in the presence of anti-CD147 mAbs. The mAb M6-1E9 inhibited T cell functions via activation of CD147 on monocytes with obligatory cell-cell contact. Engagement of the CD147 epitope by the M6-1E9 mAb downregulated CD80 and CD86 expression on monocytes and IL-2, TNF-, IFN- and IL-17 production in T cells. In contrast, the mAb M6-1D4 inhibited T cell function via activation of CD147 on T cells by downregulating IL-2, TNF- and IFN-. Herein, we demonstrated that certain epitopes of CD147, expressed on both monocytes and T cells, are involved in the regulation of T cell activation.